Exposed crystal facet tuning of CeO2 for boosting catalytic soot combustion: The effect of La dopant. Issue 5 (October 2022) - Zhao, Peng; Feng, Nengjie; Tan, Bangjie; Huo, Zhuobin; Liu, Geng; Wan, Hui; Guan, Guofeng
Abstract: The exposed crystal facets are crucial to heterogeneous catalysis. Herein, the facet controlled Ce1−x Lax Oδ (0 ≤ x ≤ 0.30) nanocomposites have been constructed elaborately via a hydrothermal route and used for soot abatement. The catalysts were characterized by XRD, TEM, Raman, FT-IR, XPS, H2 -TPR, and so forth. With the increasing content of La 3+, part of CeO2 crystals transformed from nanocubes to nanorods, inducing distinct effects on the catalytic activity. When the concentration of La 3+ was lower than 10 %, the exposed facet in the catalyst was (200). After La 3+ were further introduced, the facet degraded to (111). La 3+ at low concentration would enhance activity by facilitating lattice oxygen delivery and inducing abundant surface oxygen species, especially O -, which were vital to surface sensitive soot oxidation. Nevertheless, excessive La 3+ ions would inhibit CO2 desorption due to the generation of La2 O2 CO3, a strong alkali as a result of phase separation. Among all the catalysts, Ce0.95 La0.05 Oδ showed the best catalytic performances for soot combustion, with T50 of 375 °C. Graphical Abstract: ga1 Highlights: La 3+ ions modulate morphologies and exposed facet of Ce1- x La x Oδ catalysts. La 3+ ions strengthen resistance against thermal sintering. Ce0.95 La0.05 Oδ was excellent due to oxygen vacancies and abundant O - species. Moisture improved soot oxidation via hydroxyl adsorption on oxygen vacancies.